Oikonimy of Ukraine: ecolinguistic discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the condition of the Ukrainian oikonimy of the second part of XXth century in the light of ecolinguistics.The influence of extra- and interlingual factors on the naming of the settlements throughout Ukraine is defined. The inobservance of the Ukarainian official language norms while renaming of the villages, towns and cities of Ukraine in Soviet times is proved illustratively.
Keywords: ecolinguistics; language norms; oikonimy